Evaluation of the Anxiolytic and Anti-Epileptogenic Potential of Lactuca Serriola Seed Using Pentylenetetrazol-Induced Kindling in Mice and Metabolic Profiling of Its Bioactive Extract - Muhammad Ihsan Ullah; Rukhsana Anwar; Shahzad Kamran; Bazgha Gul; Sameh S. Elhady; Fadia S. Youssef (MDPI AG, 2022)
This study aimed to assess the potential of Lactuca serriola (Asteraceae) seed n-hexane, chloroform, methanol, and aqueous extracts as anticonvulsant, sedative, anticonvulsant and antiepileptic agents in Swiss albino mice. Different doses of each extract were evaluated for the anxiolytic potential using the hole-board, the elevated plus maze and the light/dark test. A phenobarbitone-induced sleep test was employed for the evaluation of sedative potential. Acute anticonvulsant activity was evaluated by picrotoxin and strychnine-induced convulsion models. All extracts significantly reduced the number of head dips where n-hexane extract (400 mg/kg) showed 96.34% reduction in the tendency of head dipping when compared with the control. Mice treated with extracts preferred elevated plus maze open arms and were shown to lack open arms evasion, especially n-hexane extract (400 mg/kg)-which showed 456.14%-increased the duration of open arm stay with the respective control group. By reducing sleep latency and greatly lengthening sleep duration, L. serriola enhanced the effects of barbiturate-induced sleep. A significant increase in convulsion latency and decrease in convulsions induced by picrotoxin and strychnine duration was observed in all extract-treated groups. All the extracts exhibited anti-epileptogenic potential as the seizure score in pentylenetetrazol (PTZ)-induced kindling in mice was reduced significantly. Maximum protection was afforded by chloroform extract that reduced the seizure score by 79.93% compared with the PTZ group. Chloroform executed antioxidant effect by elevating super oxide dismutase (SOD) by 126%, catalase (CAT) by 83.53%, total glutathione (tGSH) by 149%, and reducing malondialdhyde (MDA) levels by 36.49% in the brain tissues that is further consolidated by histopathological examination. Metabolic profiling of the most active chloroform extract using Gas chromatography coupled with mass showed the presence of 16 compounds. This anti-epileptic activity was further confirmed via in silico molecular modelling studies in the active site Gamma-aminobutyric acid aminotransferase (GABA-AT) where all of the tested metabolites illustrated a potent inhibitory potential towards GABA-AT with hexadecanoic acid, 15-methyl-, methyl ester followed by octadecanoic acid, methyl ester showed the best fitting. The results indicated the possible anxiolytic and anti-epileptogenic potential of the plant and further consolidated the ethnopharmacological use of L. serriola seeds.